2015
DOI: 10.1589/jpts.27.2275
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flexi-bar and non-flexi-bar exercises on trunk muscles activity in different postures in healthy adults

Abstract: [Purpose] The purpose of this study was to assess the effects of flexi-bar exercises and non-flexi-bar exercises on trunk muscle activity in different postures in healthy adults. [Subjects] Twenty healthy right-hand dominant adults (10 males and 10 females) were selected for this study. None of the participants had experienced any orthopedic problems in the spine or in the upper and lower extremities in the previous six months. [Methods] The subjects were instructed to adopt three exercise postures: posture 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
(16 reference statements)
0
10
0
1
Order By: Relevance
“…Vibration stimulation acts on the α-motor neurons, causes contraction of the muscle belly and tendons, and thereby gives rise to myotonic vibration reflection 15 , 16 ) . This increase in the proprioceptive sense of the muscle is thought to increase muscular activity, as it enables the muscle to carry a greater external load 17 ) . The vibration stimulation caused by the Flexi-bar exercise program stimulates the mechanical receptors of the articular capsule of the lumbar joints, enables greater control of posture and motor sense, and improves stability between spinal segments 15 , 16 , 17 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vibration stimulation acts on the α-motor neurons, causes contraction of the muscle belly and tendons, and thereby gives rise to myotonic vibration reflection 15 , 16 ) . This increase in the proprioceptive sense of the muscle is thought to increase muscular activity, as it enables the muscle to carry a greater external load 17 ) . The vibration stimulation caused by the Flexi-bar exercise program stimulates the mechanical receptors of the articular capsule of the lumbar joints, enables greater control of posture and motor sense, and improves stability between spinal segments 15 , 16 , 17 ) .…”
Section: Discussionmentioning
confidence: 99%
“…This increase in the proprioceptive sense of the muscle is thought to increase muscular activity, as it enables the muscle to carry a greater external load 17 ) . The vibration stimulation caused by the Flexi-bar exercise program stimulates the mechanical receptors of the articular capsule of the lumbar joints, enables greater control of posture and motor sense, and improves stability between spinal segments 15 , 16 , 17 ) . This study showed that vibration exercise using shoulder joint facilitated proprioception and had an influence on trunk stabilization, and had a positive influence on decreasing the pain and improving the functional disorder of low back pain patients.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Chung et al. 16 ) reported different results for the effect of the Flexi-Bar exercise on the activation of trunk muscles. The Flexi-Bar exercise showed greater external weight effect compared to the use of a non-vibrating bar, with clear differences in the activation of the internal oblique and external oblique muscles.…”
Section: Discussionmentioning
confidence: 95%
“…24 These results were consistent with a previous study that showed that quadruped, standing, and side-bridging positions with a fleixbar was associated with higher IO muscles activation. 19 Goncalves et al 25 reported that the IO muscles presented a 72% greater muscle activity during the exercises performed with a flexible pole than with a non-flexible pole.…”
Section: Resultsmentioning
confidence: 99%
“…Chung et al 19 suggested that surface electromyography of selected trunk muscles was measured with RA, EO, IO, and ES muscle in quadruped, sidebridging, and standing positions, so that flexible pole exercises are useful in the activation of trunk muscles.…”
Section: J Kptmentioning
confidence: 99%